The Influence of Intrinsic Motivation and Extrinsic Motivation on Employee Performance Productivity of PT. Weigh Deli Indonesia - Triswanto, Hadi; Lidia Yunita (Journal of Economics and Business (JECOMBI), 2022)
This study aims to determine the effect of intrinsic motivation and extrinsic motivation on the productivity of employee performance at PT. Weigh Deli Indonesia and to find out the dominant variable on the productivity of the employee performance of PT. Weigh Deli Indonesia. This study uses employees of PT. Weigh Deli Indonesia as a sample which is dominated by the age range of 31 - 40 years and length of work less than 10 years, totaling 139 people. The primary data in this study is a questionnaire that has been filled in by employees of PT. Weigh Deli Indonesia. Based on the results of the study showed that partially intrinsic motivation has a positive and significant effect on employee performance productivity, while extrinsic motivation has no significant effect on employee performance productivity. Simultaneously, intrinsic motivation and extrinsic motivation together have a positive and significant effect on employee performance productivity. Intrinsic motivation and extrinsic motivation have a sufficient correlation with productivity, and performance productivity can be explained by intrinsic motivation and extrinsic motivation by 41.2% and the remaining 58.8% can be explained by other variables not examined.